Hydrothermal synthesis of mixtures of NaA zeolite and sodalite from Ti-bearing electric arc furnace slag. Issue 10 (20th January 2016) - Li, Yang; Peng, Tiehong; Man, Wenkuan; Ju, Liangchen; Zheng, Feng; Zhang, Mei; Guo, Min
Abstract : NaA and sodalite zeolites were synthesized from Ti-bearing EAF slag and the removal capacity of prepared zeolite for Cu 2+ can reach 1.346 mmol g −1 for 180 min. Abstract : Ti-bearing electric arc furnace slag (Ti-bearing EAF slag) is the main solid waste generated in the direct reduction iron making process. During the extraction process of Ti from Ti-bearing EAF slag, a by-product containing abundant Si and Al was seldom utilized, thus leading to waste of valuable elements and secondary pollution. In this paper, NaA zeolite (6Na2 O·6Al2 O3 ·12SiO2 ) and sodalite (SOD, 4Na2 O·3Al2 O3 ·6SiO2 ) were synthesized successfully using the by-product as a precursor. The effects of the SiO2 /Al2 O3 molar ratio ( n (SiO2 )/ n (Al2 O3 )), H2 O/Na2 O molar ratio ( n (H2 O)/ n (Na2 O)), hydrothermal temperature and time on the crystal phase and microstructure of the prepared zeolites were systematically investigated. The results indicated that NaA zeolite with good crystallinity and cubic morphology was obtained at 140 °C for 3 h with n (SiO2 )/ n (Al2 O3 ) and n (H2 O)/ n (Na2 O) fixed at 2.0 : 1 and 100 : 1, respectively. Decreasing n (H2 O)/ n (Na2 O), raising the hydrothermal temperature and prolonging the hydrothermal time were beneficial for the formation of spherical SOD zeolite. The phase transformation between NaA and SOD zeolite was discussed and a mechanism was proposed to explain the phenomenon of these zeolites coexisting in the obtained samples. In addition, the removal performances of Cu 2+ in aqueous solutions using zeolites synthesized at different temperatures were studied. The maximum removal capacity of the prepared zeolite can reach 1.346 mmol g −1 for 180 min.